2014
DOI: 10.1186/1756-3305-7-347
|View full text |Cite
|
Sign up to set email alerts
|

Field clinical study evaluating the efficacy and safety of an oral formulation containing milbemycin oxime/praziquantel (Milbemax®, Novartis Animal Health) in the chemoprevention of the zoonotic canine infection by Dirofilaria repens

Abstract: BackgroundDirofilaria repens is the causative agent of subcutaneous dirofilariosis of dogs, other animals and humans. This nematode is transmitted by mosquitoes of Aedes, Anopheles and Culex genera. In dogs, the parasite may cause subclinical infection or cutaneous signs. Recently, D. repens has emerged and spread in different geographical areas, with an increase of cases in dogs and humans. Chemoprevention in dogs in endemic areas is the most reliable approach for controlling this infection. This paper descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Finally, milbemycin oxime, another macrocyclic lactone, given orally once per month also proved to be effective in protecting dogs from subcutaneous dirofilariosis in endemic areas and may offer further chemoprevention option [277].…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…Finally, milbemycin oxime, another macrocyclic lactone, given orally once per month also proved to be effective in protecting dogs from subcutaneous dirofilariosis in endemic areas and may offer further chemoprevention option [277].…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…None of the dogs treated monthly with the recommended dose became microfilaraemic, while 6 of 114 control dogs became infected. All positive dogs were successfully treated with milbemycin oxime, but the exact treatment protocol was not described (Di Cesare et al 2014). Oral and injectable formulations of moxidectin have shown preventive efficacy against D. repens in field studies (Rossi et al 2002(Rossi et al , 2004, and the efficacy of an injectable sustained-release formulation was confirmed in experimentally infected dogs (Genchi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the synergistic effect due to the simultaneous combination of a macrocyclic lactone and a parasiticide-repellent product provides better protection against CVBDs and in particular against MBHs, with respect to which both products are active. The combination milbemycin oxime/praziquantel, like other macrocyclic lactones, was designed to prevent dirofilarial infections in dogs [33]. DPP has a proven record of effectiveness in preventing a broad spectrum of vectors such as ticks, mosquitoes, sandflies, stable flies, fleas and triatomes [15][16][17], and this partly explains the successful prevention of the other CVBDs in the present study.…”
Section: Discussionmentioning
confidence: 94%